2005
DOI: 10.1159/000083976
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Modified Allergen Extracts by in vitro β-Hexosaminidase Release from Rat Basophils

Abstract: Background: To date, there is no well-established test available that can be used to measure functional properties of modified allergens (allergoids). Due to the cross-linking process, the IgE-binding capacity of the allergens, normally necessary for their characterization, is lost. The aim of this study was to test whether the rat basophilic leukaemia (RBL) cell assay (β-hexosaminidase release by rat basophils upon allergen stimulation) can be adopted to characterize allergoids and to evaluate the assay for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…These reports all conclude that allergoids show reduced allergenicity in IgE binding and IgE inhibition assays, different basophil activation tests, or skin tests [10,13,14,15]. This was confirmed in the present study (fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These reports all conclude that allergoids show reduced allergenicity in IgE binding and IgE inhibition assays, different basophil activation tests, or skin tests [10,13,14,15]. This was confirmed in the present study (fig.…”
Section: Discussionsupporting
confidence: 91%
“…Studies of allergoids have demonstrated reduced allergenicity by various in vitro methods as well as skin prick testing [10,13,14,15], and treatment with allergoids has shown efficacy in reducing symptom and medication scores in some studies [7, 8]. However, the clinical effect of allergoids may be compromised because they seem to lack the ability to modify allergen-specific T cell responses [12, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vitro Mediator Release Assay with Humanized Rat Basophilic Leukemia Cells (RBL-SX38)-In vitro degranulation was analyzed as described previously (27). Soluble ␣-Gal proteins were biotinylated using TFPA-PEG3-biotin (tetrafluorophenylazide-(triethyleneglycol)-biotin (Pierce) according to the recommendations of the manufacturer and incubated with streptavidin-coated Roti-MagBeads (Roth).…”
Section: Methodsmentioning
confidence: 99%
“…After washing twice with Tyrode buffer (pH 7.7), the cells were incubated with 120 l/well of Tyrode buffer containing 10 g/ml DNP-BSA (Molecular Probes, Eugene, OR) for 30 min. The released ␤-hexosaminidase was measured (22).…”
Section: Methodsmentioning
confidence: 99%